BIAYA OPERASIONAL KENDARAAN TAKSI ONLINE DI KOTA PALANGKA RAYA (STUDI KASUS: GOCAR) - Nakalelo, Melky; Murniati, Murniati; Desiriani, Desiriani (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
One of the online transportation that has increased its use in the City of Palangka Raya, one of which is an online taxi, one of which is Gocar. Gocar is in great demand by the public because of its competitive rates and more affordable rates than its competitors. The Ministry of Transportation has set an upper and lower limit for the Kalimantan region, it is between Rp.3,700 - Rp.6,500 per kilometer. The purpose of this study is to analyze the tariffs for Gocar and Gocar L based on vehicle operating costs to get how much the standard tariff for Gocar and Gocar L is in Palangka Raya City. The method used to calculate vehicle operating costs and tariffs is the 2002 Directorate General of Land Transportation method. The results show that Gocar and Gocar L rates based on the 2002 Directorate General of Land Transportation method are above the current rates, for Gocar, Honda Brio CVT (2021 ) Rp.14,110, Toyota Agya 1.2 MT (2022) Rp.10,203 and Daihatsu Ayla 1.2 MT (2020) Rp.11,981 and for Gocar L, Honda Mobilio MT (2018) Rp. 11,368, Toyota Calya 1.2 MT (2022) of IDR 7,561 and Daihatsu Sigra 1.2 MT (2018) of IDR 14,672 where the applicable tariff is IDR 5,024 – IDR 5,560 per km, with lower limit rates and upper limit rates ie IDR 3,700 – 6,500 per km.